Identification of gastrointestinal parasites in pig farms and economic losses due to condemnation of livers parasitized by Ascaris suum in abattoirs in Costa Rica - Zumbado, Leana (2013)
The purpose of this study was to identify the gastrointestinal parasites (GIP) and control practices from nine pig farms in Costa Rica,and to determine the economic impact due to condemnation of pig livers with lesions related to migration of Ascaris suum in the great metropolitan area. Overall, 538 fecal samples were collected at convenience from the different groups: early pregnancy, late pregnancy, lactation, initiation, development, fattening boars. To determine the economic losses due to A. suum official records from the Ministerio de Agricultura y Ganadería (MAG) and four slaughterhouses from the great metropolitan area (2002-2008) were analyzed. The following GIP were detected in 405 (75.3%) fecal samples: Coccidia (98.2%), Strongyloides ransomi (8.1%), Trichuris suis (7.2%), A. suum (1.7%) and Strongylida (0.5%). These results were not expected since antiparasitic products were used regularly (intermittent or continuous use). From 2002-2008, the presence of “milk spots” was the most common cause of condemnation of pig livers (73.1%), resulting in economic losses amounting to ¢ 178,231,617 ($ 314,897). The results indicate the need to change some practices in order to achieve adequate control for GIP.